The Effect Of Abdominal Stretching Exercises On The Intensity Of Menstrual Pain (Dysmenorrhea) In Young Woman In Adolescent Women - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Basyariah Lubis; Riri Safitri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Dysmenorrhea is pain that occurs during menstruation and is often experienced by adolescents. Reduced pain can interfere with the daily activities of teenagers. Based on an initial survey conducted by researchers at SMK AL-Washliyah 9 Perbaungan on 6 students, the researchers conducted interviews with students who were experiencing dysmenorrhea, often asking permission to go to the UKS room and even going home because of the pain caused by dysmenorrhea which greatly interfered with the learning process and activities other. To overcome this, one of the non-pharmacological alternatives is Abdominal Stretching exercises that can provide a relaxing effect, so that it can be used to treat pain during menstruation. The purpose of this study was to determine whether or not there was a decrease in pain intensity in adolescent girls before performing Abdominal Stretching exercises and after Abdominal Stretching exercises. This type of research is pre-experimental in one group (one group pre-test and post-test). The sample of this study was taken by purposive sampling technique, namely sampling based on specified criteria. The sample in this study amounted to 22 people. This research was conducted in June 2022. Data analysis used the Saphiro Wilk test. The research instrument used was a pain observation sheet, namely the Numeric Rating Scale (NRS). The results showed that the average pain scale before treatment was 2.59 then reduced to 1.50 after the Abdominal Stretching exercise was performed. The calculated Z value is 4.233 and the p-value is 0.000, thus p-value<? (0.000<0.05). This shows that there is a significant difference in the dysmenorrhea pain scale of adolescent girls before and after the Abdominal Stretching exercise.